The role of Small and Medium-Sized hotel development in the sustainable development of mountainous regions (on the example of the Adjara Region) - Katsitadze, Nana; Aladashvili, Manana; Kochlamazashvili, Lela; Tushishvili, Natela (Goodwood Publishing, 2025)
Abstract Purpose: The purpose of the research is to identify the features of the development of the hotel business in the mountainous zone of Adjara and the factors facilitating and hindering its further development; to determine the strategic directions of the hotel business in Upper Adjara in order to achieve sustainable development of the tourism industry. Methodology: The research employed a mixed-method approach, combining qualitative and quantitative methodologies to explore the development of hotel-type accommodation facilities in the mountainous zone of Adjara. Surveys, interviews with hotel managers and owners, and field observations were conducted to assess challenges, opportunities, infrastructure conditions, and investment potential, while secondary data analysis examined tourism policies and economic trends. Results: The survey results indicate that the hotel and guest house sector in the mountainous zone of Adjara plays a crucial role in local employment, with most small hotels employing between 3 to 10 people and guest houses increasingly relying on hired labor. However, a major challenge in the sector is the shortage of qualified personnel, as 72% of respondents struggle to find skilled employees, while interest in staff training programs remains low. Conclusions: This study confirms that the development of hotel-type accommodation facilities in the mountainous zone of Adjara is influenced by natural potential, infrastructure, and increasing tourist inflows. The role of family hotels is particularly significant, as they contribute to regional tourism by integrating local traditions and resources, though territorial imbalances in hotel distribution persist. Limitations: One limitation of this study is the lack of long-term data on the sustainability of hotel businesses in the mountainous regions, as well as the limited focus on the economic impact of branded hotels on local businesses. Contributions: This study provides a comprehensive analysis of the trends and challenges in developing hotel-type accommodation in the mountainous zone of Adjara, highlighting its economic, social, and environmental significance. It offers valuable insights into the role of family hotels in regional tourism and the impact of state policies on business sustainability.